Meaning the Values of Onang-Onang Voice at the Manortor's Tradition - Yusni Khairul Amri; Dian Marisha Putri (Budapest International Research and Critics University, 2022)
The margondang ceremony is completed with panaekkon gondang to open the galanggang 'na so marongit, tapian na so marlinta' which is followed by a manortor ceremony accompanied by onang-onang poetry. Poems sung by paronang-onang accompanied by gondang instrumental music at traditional ceremonies. The data of onang-onang poetry was taken at the Angkola traditional marriage ceremony, in the city of Medan. Barthes (1957:140-142) uses the concept of value according to Barthes (1957:140-142), namely: 1) values related to the subject; 2) values appear in a practical context; 3) value concerns the properties that are 'added' by the subject. taken based on the analysis data classified the results of the analysis of the values of the Angkola traditional onang-onang poetry, among others: the values contained in the lyrics of the Angkola traditional onang-onang poems include: 1. Values Relating to the Subject: a) The Value of Parental Love for Children and Son-in-law b) Advice for Living in harmony, c) Maintaining kinship relations. 2. Values appear in a practical context: a) Belief in the Almighty, b) Forms of Parental Love. 3. The Value of the Characteristics 'Added' by the Subject: a) Angkola Identity Value, and b) Aesthetic Value